The Impact of Market Orientation Components on Organizational Performance of SMEs. The single-industry approach " Food and Beverage Sector" - Abdulsamad, Akram; ALI, Noor Azman; Mahomed, Anuar Shah Bali; Hashim, Haslinda; Jandab, Abdulwahab; Hamdan, Abdalkrim; Al-Sharif, Abdulrahman M. (Advances in Social Sciences Research Journal, 2021)
This study examines the direct effect of the three main components of the market orientation on the organizational performance of SMEs in Yemen. Four variables are used in the research, are competitor orientation, customer orientation, and inter-functional coordination, as the exogenous latent variables, whereas organizational performance, as the endogenous latent variable. The quantitative approach is applied in this study with causal and descriptive research. The single-sector method is adopted, is the food and beverage sector, by using random sample sampling, the sample size was 640 managers/owners. only 459 samples were valid to conduct the analysis by using the Structural Equation Model (SEM) in SmartPLS Software version 3.0. The findings of the study reveal that the three main components of the market orientation have a positive and significant impact on SMEs’ organizational performance. However, the effect size of customer orientation on organizational performance was more than competitor orientation and inter-functional coordination.